RANCANG BANGUN PERALATAN PENGAMAN PADA TOKO PERHIASAN BERBASIS ARDUINO - Hani Dewi Ariessanti; Indrianto Indrianto; Rifan Munzilin (Universitas Raharja, 2015)
With increasing human needs in terms of security , especially in securing the jewelry store then made a design that resembles the display of safety equipment . The working principle of safety equipment on this arduino -based jewelry store is by using infrared sensors to transmit data at the next arduino electric current is converted into mechanical motion of the dc motor , the next shipment via bluetooth character code that is processed in the microcontroller into a form of decision . The method is obtainable design technique that consists of : Identify the need is to identify the needs of what is needed in the manufacture of tools, Analysis of the needs is to analyze all the needs of the tool before the tool design process, The design of the hardware and software that is designing and preparing the materials are to be used to make tools, Preparation of tools that process of unification of all materials to form tools and, Testing tools that test the performance of the tool